2015
DOI: 10.1016/j.ijosm.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The Osteopathic Clinical Practice Assessment – a pilot study to develop a new workplace-based assessment tool

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The implementation and use of a single assessment tool to assess specific skills (e.g., competency in a clinical or procedural task) in specific types of clinical learning environments (e.g., a single clinical unit or department) was the most commonly implemented form of WBA found in our review, with a total of 31 pilot studies. 22–53 While individual WBA tools were the most commonly studied, 26 papers discussed implementing pilots of programmatic assessment, where multiple individual assessment tools are used by multiple assessors in different contexts to support an educational design. 52,54–57 Since 2005 when programmatic assessment was defined, programs of assessment primarily have been built to support undergraduate medical education (UME) curriculums, although some studies reported its use in GME contexts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation and use of a single assessment tool to assess specific skills (e.g., competency in a clinical or procedural task) in specific types of clinical learning environments (e.g., a single clinical unit or department) was the most commonly implemented form of WBA found in our review, with a total of 31 pilot studies. 22–53 While individual WBA tools were the most commonly studied, 26 papers discussed implementing pilots of programmatic assessment, where multiple individual assessment tools are used by multiple assessors in different contexts to support an educational design. 52,54–57 Since 2005 when programmatic assessment was defined, programs of assessment primarily have been built to support undergraduate medical education (UME) curriculums, although some studies reported its use in GME contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Studies investigated aspects of validity most commonly, with the majority of studies concluding that the relevant tool was valid for its intended purpose. 22,25,26,30,33,36,37,39,45,46,48,50,53–75 Eight studies investigated the use and implementation of multisource feedback tools, which were the most prevalent type of implemented tool. 46,54,55,59,60,62,63,68 Several papers emphasized the importance of including the viewpoints of multiple assessors in the clinical learning environment and the importance of collecting both quantitative and qualitative data in assessment tools.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within osteopathy, however, little is published about OPI or its development (OPID). Initiatives in the International Journal of Osteopathic Medicine (IJOM) have undoubtedly raised the profile of osteopathic education research [39][40][41], but this has often focused on practical issues such as student assessment [42][43][44] and learning resources [45][46][47]. A search of IJOM, from inception to present, revealed only three examples of peer-reviewed primary research with explicit OPI focus [23,24,48], although there are some discussion papers [39,[49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%